Pendugaan laju run off dan infiltrasi dengan rainfall simulator sederhana pada berbagai kondisi tanah Andisol di perkebunan teh - Restu Wulansari; Erdiansyah Rezamela; Augusthyne Chrismonera N.P.L (Jurnal Pengelolaan Perkebunan (JPP), 2021)
Many tea plantations are planted on several slopes, this has the potential for soil erosion.Â  Eroded soil will cause a decrease in soil fertility and tea plant productivity. The ability of the soil in tea plantations needs to be tested against the run-off rate in laboratory experiments using a tool called a simple rainfall simulator (simulation of artificial rain). The study used a factorial randomized block design consisting of 2 factors, factor 1 (soil media) and factor 2 (rainfall) with 3 replications. Observation parameters are run off rate and infiltration volume. The results showed that the interaction of soil media with rainfall significantly affected the run off rate. Rainfall intensity >100 mm with andisol soil + manure showed a run off rate of 77% higher than andisol soil. The less land cover on the soil media, the higher the run off rate. In the treatment of andisol soil + manure gave the lowest infiltration volume. The denser the land cover vegetation and organic matter content, the more effective it is in protecting the soil surface from erosion because it can increase water absorption by the soil.